Software tool used for automated design of customizable product - Pescaru, Roxana; Kyratsis, Panagiotis; Oancea, Gheorghe (EDP Sciences, 2017)
The paper presents an original software tool implemented for an automated design methodology associated to a customizable product from footwear industry. The software tool is written in Visual Basic for Application and is integrated in CATIA environment. It is an easy to use software tool and combines reverse engineering with parametric design of a product that has complex shapes with many curves. The final result is a solid CAD model obtained in an automatically mode.